Dispute Resolution of Debtor Default in Working Capital Credit Agreements at PT BPR Kredit Mandiri Indonesia - Amanda Fitra Hamzah; Yasmin Fakhira Khairatun Hisan; Audri Razan Anargya; Dwi Desi Yayi Tarina (Media Hukum Indonesia (MHI), 2026)
This study was motivated by the increasing risk of default in banking credit agreements, particularly in Working Capital Loan as well as the application of collateral seizure as legal protection for creditors. This study employs a normative legal method, analyzing Judgment No. 2/Pdt.G.S/2024/PN. Cbn, within a conceptual framework. The findings indicate that dispute resolution proceeds through a tiered process, ranging from non-litigation channels to litigation channels. The application of collateral seizure in this dispute resolution serves as a crucial instrument to secure the Debtor’s property rights and ensure the effectiveness of court decision enforcement by implementing the principle of banking prudence. This enables the optimization of credit agreement dispute resolution in a proportional manner and based on concrete evidence to maintain balance, justice, and legal certainty between the Creditor and the Debtor.